1978
DOI: 10.1111/j.1471-4159.1978.tb06577.x
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF (Na+‐K+)‐ATPase IN RAT CEREBRUM: CORRELATION WITH Na + ‐DEPENDENT PHOSPHORYLATION AND K +para NITROPHENYLPHOSPHATASE1

Abstract: Abstract— The activities of (Na+ K+)‐ATPase and its proposed partial reactions, K +‐pNPPase and Na +‐dependent phosphorylation, all increase tenfold relative to microsomal protein between 5 days prior to birth and 60 days postnatally in NaI‐treated rat cerebral microsomes, and all reach half of their adult values between the fifth and tenth postnatal day. These increases are concurrent with the most rapid changes in cerebral wet weight. Increases in the amount of the related phosphorylatable polypeptide during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…They hypothesized that this effect is dependent on extracellular adenosine concentrations, cell surface expression of different adenosine receptor subtypes, and signal transduction mechanisms activated following the binding of specific agonists. In developing rat brain, there is an increase in the activities of Na + , K + ‐ATPase (Valcana and Timiras, 1969; Bertoni and Siegel, 1978; Ahmed et al, 2010; Ahmed, 2012a), Ca 2+ ‐ATPase and Mg 2+ ‐ATPase (Ahmed et al, 2010; Ahmed, 2012a). The increases in pump activities are accompanied by a change in the brain's ionic composition (Valcana and Timiras, 1969; dos Reis‐Lunardelli et al, 2007) and a greater number of functional sodium pump sites (Bertoni and Siegel, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that this effect is dependent on extracellular adenosine concentrations, cell surface expression of different adenosine receptor subtypes, and signal transduction mechanisms activated following the binding of specific agonists. In developing rat brain, there is an increase in the activities of Na + , K + ‐ATPase (Valcana and Timiras, 1969; Bertoni and Siegel, 1978; Ahmed et al, 2010; Ahmed, 2012a), Ca 2+ ‐ATPase and Mg 2+ ‐ATPase (Ahmed et al, 2010; Ahmed, 2012a). The increases in pump activities are accompanied by a change in the brain's ionic composition (Valcana and Timiras, 1969; dos Reis‐Lunardelli et al, 2007) and a greater number of functional sodium pump sites (Bertoni and Siegel, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…ATPase‐enzyme (Na + ,K + ‐ATPase, Ca 2+ ‐ATPase and Mg 2+ ‐ATPase) activities of control rat offspring were stepwisely increased in all investigated regions with the age progress. During development, there is an increase in Na + ,K + ‐ATPase activity in the rat brain (Bertoni and Siegel, 1978) accompanied by a marked change in the brain's ionic composition (Valcana and Timiras, 1969) and increase in the number of functional sodium pump sites (Bertoni and Siegel, 1978). Notably, Valcana and Timiras (1969) have shown that a component of the increase in Na + ,K + ‐ATPase activity in developing rat brain is due to the presence of THs.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of evidence demonstrates a relationship between cellular proliferation and maturation and the activity of the Na,K-ATPase (Kennedy and Lever, 1984;Smith and Rozengurt, 1978). The activity of this enzyme responsible for the active Na-K transport across the nerve cell membrane (Stahl, 1986) increases with neuronal differentiation (Atterwill et al, 1984;Bertoni and Siegel, 1978;Blanco and Beauge, 1988). Moreover, the relative expression of the various isoforms of the Na,K-ATPasc demonstrated in nervous tissue (Blanco and Beau&, 1988;Matsuda et al, 1984;Shull et al, 1986;Sweadner, 1989) seems to be dependent on the dcvelopmental stage (Blanco andBeauge, 1988: Matsuda et al, 1984).…”
Section: Introductionmentioning
confidence: 99%